TESTES DE SENSIBILIDADE E CONSTRUÇÃO DE CASSETE DE EXPRESSÃO VISANDO O SILENCIAMENTO GENICO DO RECEPTOR DE ETILENO FaETR1 EM Fragaria x ananassa L. Duch. - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
significant world production. The true fruits of the strawberry are dry and called achenes while the fleshy and edible portion actually it is the floral receptacle developed. This set of achene and receptacle features the non-climacteric fruit pattern ripening, characterized by not show a peak respiration and ethylene production during the ripening process and also for this fruits not being able to complete the ripening after harvesting. Due to the small size of the plant, rapid propagation and production of fruit, the strawberry became the model plant in studies of non- climacteric fruit ripening, particularly with regard to the ethylene role in this process. Fruit ripening the focused studies have revealed the existence of a family of protein receptors responsible for the plant ethylene perception. In strawberry, have been identified so far three ethylene receptors genes sequences, divided into two subfamilies (FaETR1 and FaERS1 - subfamily I and FaERS2 - subfamily II). Among these genes, based on the literature, we believe that FaETR1 gene, a member of the ethylene receptors subfamily I, can develop a greater role to the other receptors in the control of perception and ethylene signal transduction. To assess the involvement of FaETR1 ethylene receptor in the strawberry ripening and toward an understanding of the relationship between ethylene and nonclimacteric fruits ripening, we seek the silencing of this particular gene. Thus, the objective of this work was the construction of a binary plasmid structure in hairpin format (hpRNA) that induces the activation of RNA interference system (RNAi) on the translation of FaETR1 gene in ethylene receptor protein. Also, knowing the importance of an appropriate regeneration an plant transformed selection method, we seek also develop a proper in vitro regeneration protocol of Camino Real and Festival strawberries cultivar, as well as to assess the sensitivity of these plants to kanamycin (antibiotic) and glufosinate ammonium (herbicide) selective agents, whose genes are present in pCAMBIA 3301 and pCAMBIA2301 cloning vectors used in this study.
Keywords: Fragaria x ananassa; Silenciamento gênico; organogenese e cultura de tecidos; Fragaria x ananassa; gene silencing; organogenesis and tissue culture; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA